Beneficial role of insect-derived bioactive components against inflammation and its associated complications (colitis and arthritis) and cancer. (1st November 2019) - Dutta, Prachurjya; Sahu, Ravi Kumar; Dey, Tapan; Lahkar, Manisha Datta; Manna, Prasenjit; Kalita, Jatin
Abstract: Insect-based bioactive components are emerging as novel sources of drugs, effective against various diseases. Inflammation is considered to be an innate immune response developed by different organisms against foreign pathogens and cellular stress. However, repetitive elevated inflammation is considered to be responsible for development of many other diseases including colitis and arthritis. Due to the limited activities and side effects of non-steroidal anti-inflammatory drugs, researchers are continuously looking for alternative sources of drug molecules to alleviate the inflammatory related complications. Recently, insect-based bioactive components, such as venoms, haemocytes, cecropin A, papiliocin, N-acetyldopamine dimers, cecropin-TY1 peptide, cop A3 peptide, glycosaminoglycan, coprisin peptide, silk fibroin microparticles, and silk fibroin nanoparticles have been found to be active against different inflammatory mechanisms and associated diseases. Cancers, are some of the deadliest diseases, which are mainly treated by chemotherapy, radiation therapy and surgery. However, such treatments, mainly chemotherapy, is associated with enormous side effects. Therefore, as an alternative, less hazardous option, compounds from insects with anti-cancerous activity are being explored. Insect-derived compounds, such as cantharidin, norcantharidin, isocoumarin, plancyols A, plancypyrazine A, pancratistatin, narciclasine, and ungeremine, show potential anti-cancerous activity. In this review, we will be discussing the role of different potential drug molecules of insect origin with special emphasis on anti-inflammation and their association with health disorders and cancer. Graphical abstract: Image 1